Development of influenza A(H7N9) candidate vaccine viruses with improved hemagglutinin antigen yield in eggs. Issue 5 (September 2015) - Ridenour, Callie; Johnson, Adam; Winne, Emily; Hossain, Jaber; Mateu‐Petit, Guaniri; Balish, Amanda; Santana, Wanda; Kim, Taejoong; Davis, Charles; Cox, Nancy J.; Barr, John R.; Donis, Ruben O.; et al.
<x xml:space="preserve">Abstract</x> Background The emergence of avian influenza A(H7N9) virus in poultry causing zoonotic human infections was reported on March 31, 2013. Development of A(H7N9) candidate vaccine viruses (CVV) for pandemic preparedness purposes was initiated without delay. Candidate vaccine viruses were derived by reverse genetics using the internal genes of A/Puerto/Rico/8/34 (PR8). The resulting A(H7N9) CVVs needed improvement because they had titers and antigen yields that were suboptimal for vaccine manufacturing in eggs, especially in a pandemic situation. Methods Two CVVs derived by reverse genetics were serially passaged in embryonated eggs to improve the hemagglutinin (HA) antigen yield. The total viral protein and HA antigen yields of six egg‐passaged CVVs were determined by the BCA assay and isotope dilution mass spectrometry (IDMS) analysis, respectively. CVVs were antigenically characterized by hemagglutination inhibition (HI) assays with ferret antisera. Results Improvement of total viral protein yield was observed for the six egg‐passaged CVVs; HA quantification by IDMS indicated approximately a twofold increase in yield of several egg‐passaged viruses as compared to that of the parental CVV. Several different amino acid substitutions were identified in the HA of all viruses after serial passage. However, HI tests indicated that the antigenic properties of two CVVs remained unchanged. Conclusions If influenza A(H7N9) viruses were to acquire sustained human‐to‐human transmissibility, the improved HA yield of the egg‐passaged CVVs generated in this study could expedite vaccine manufacturing for pandemic mitigation.